Phenomenological Analysis of the Trope Pasar a Llevar [Análisis Fenomenológico del Tropo Pasar a Llevar] - Contreras-Salinas, S (Universidad de Concepcion, 2017)
This article reports the findings of an ethnographic study whose objective was to appreciate some defining tropes of the existential concerns that are constructed in everyday life of a family that inhabits an urbanised rural area. From here we delve into the trope pasar a llevar which proved a very fruitful research parameter when illustrating various aspects, especially the phenomenology of inequality and exclusion, from its use as unquestionable data in the series of arguments that are revealed in their narratives, building knowledge that is configured in various practices.